Building accessible websites - Clark, Joe, 1965- (New Riders, 2003)
"Building Accessible Websites teaches how and why to use Web accessibility techniques, with an emphasis on phased accessibility that scales to the needs of small, medium, and large budgets. Whether you're an individual developer running a hobby site or the head of a large corporate Web team, Building Accessible Websites shows you affordable, technically manageable ways to make a Website accessible to people with disabilities."--BOOK JACKET.